At5g50600 encodes a member of the short-chain dehydrogenase reductase superfamily with 11beta- and 17beta-hydroxysteroid dehydrogenase activities associated with Arabidopsis thaliana seed oil bodies - d'Andréa, S; Canonge, M; Beopoulos, A; Jolivet, P; Hartmann, M A; Miquel, M; Lepiniec, L; Chardot, T (Biochimie, 2007)
In a previous work, we presented evidence for the presence of a protein encoded by At5g50600 in oil bodies (OBs) from Arabidopsis thaliana [P. Jolivet, E. Roux, S. D'Andrea, M. Davanture, L. Negroni, M. Zivy, T. Chardot, Protein composition of oil bodies in Arabidopsis thaliana ecotype WS, Plant Physiol. Biochem. 42 (2004) 501-509]. Using specific antibodies and proteomic techniques, we presently confirm the existence of this protein, which is a member of the short-chain steroid dehydrogenase reductase superfamily. We have measured its activity toward various steroids (cholesterol, dehydroepiandrosterone, cortisol, corticosterone, estradiol, estrone) and NAD(P)(H), either within purified OBs or as a purified bacterially expressed chimera. Both enzymatic systems (OBs purified from A. thaliana seeds as well as the chimeric enzyme) exhibited hydroxysteroid dehydrogenase (HSD) activity toward estradiol (17beta-hydroxysteroid) with NAD+ or NADP+, NADP+ being the preferred cofactor. Low levels of activity were observed with cortisol or corticosterone (11beta-hydroxysteroids), but neither cholesterol nor DHEA (3beta-hydroxysteroids) were substrates, whatever the cofactor used. Similar activity profiles were found for both enzyme sources. Purified OBs were found to be also able to catalyze estrone reduction (17beta-ketosteroid reductase activity) with NADPH. The enzyme occurring in A. thaliana OBs can be classified as a NADP+-dependent 11beta-,17beta-hydroxysteroid dehydrogenase/17beta-ketosteroid reductase. This enzyme probably corresponds to AtHSD1, which is encoded by At5g50600. However, its physiological role and substrates still remain to be determined.